2021
DOI: 10.1186/s12889-021-11430-3
|View full text |Cite
|
Sign up to set email alerts
|

Men’s perceptions of sexual and reproductive health education within the context of pregnancy and HIV in Zambia: a descriptive qualitative analysis

Abstract: Background Although health care providers are beginning to focus on men’s roles as fathers and husbands, there is limited understanding of how men view their ability to promote sexual and reproductive health in families affected by HIV and their experiences with receiving education through antenatal care. This paper aims to explore men’s perceptions of the education they need regarding sexual and reproductive health within the family in the context of HIV. Methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…Some mothers also reported that men believed the ECD sessions, and PMTCT services more broadly, were not meant for fathers. Our findings corroborate the previous literature in Malawi and throughout sub-Saharan Africa 29–31. In their systematic review of barriers and facilitators of male partner involvement in PMTCT, Morfaw and colleagues also found the most salient barrier to male engagement was men’s perception that PMTCT and antenatal clinics were ‘women’s spaces’, revealing that men need to be actively welcomed into these facility spaces if perceptions of female-centred services are to be overcome 30.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Some mothers also reported that men believed the ECD sessions, and PMTCT services more broadly, were not meant for fathers. Our findings corroborate the previous literature in Malawi and throughout sub-Saharan Africa 29–31. In their systematic review of barriers and facilitators of male partner involvement in PMTCT, Morfaw and colleagues also found the most salient barrier to male engagement was men’s perception that PMTCT and antenatal clinics were ‘women’s spaces’, revealing that men need to be actively welcomed into these facility spaces if perceptions of female-centred services are to be overcome 30.…”
Section: Discussionsupporting
confidence: 88%
“…-Mother of 8, age 31 Most mothers reported that their partners supported and actively implemented ECD practices at home. Mothers directly shared ECD lessons learnt from the intervention with their partner, and these lessons were put into practice by both parents.…”
Section: Fathers Valued Ecd and Increased Their Engagement With Their...mentioning
confidence: 99%
See 1 more Smart Citation
“…18 The perception that both partners should be involved in decision-making regarding healthcare differed from findings in Zambia and Nigeria, where men were seen as sole decision-makers. 18,19 Lastly, beliefs that the topic of sexuality is too private and cervical cancer screening damages the reproductive system were linked to lower male involvement in cervical cancer screening. This concurs with a study done in Botswana which revealed that these two factors were barriers to cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of normal childbirth includes an understanding of the physiological process of labor that takes place without significant medical intervention. Normal childbirth, often referred to as spontaneous labor, is a natural process in which a baby is delivered through the birth canal after the pregnancy has reached full term (37-42 weeks), with maternal labor and minimal assistance from medical personnel (Matenga, Zulu, Nkwemu, Shankalala, & ..., 2021). The process involves three main stages: the opening or dilatation phase of the cervix, the birth phase of the baby, and the birth phase of the placenta.…”
Section: Knowledge About Normal Labormentioning
confidence: 99%

Effect of  Health Education for Knowledge Pregnant Women's : Normal Delivery

Eugenia Carvalho De Araujo,
Natalia Pereira,
Etelvina Jose S. Tilman
et al. 2024
JIMR